Remarriage after divorce in today's church : 3 views - Wenham, Gordon J.; Heth, William A.; Keener, Craig S., 1960-; Strauss, Mark L. (Grand Rapids, Mich. : Zondervan, 2006)
Publisher description: A biblical and practical case for three main evangelical views on remarriage after divorce Among born-again Christians, 27 percent have experienced divorce as compared to 24 percent in the general population. Yet no consensus exists among evangelicals on their views of remarriage, leaving many Christians confused. This single volume summarizes and explores three main evangelical views: no remarriage, remarriage after adultery or desertion, and remarriage for a variety of reasons. Each of the three contributors offers his point of view succinctly with biblical support, and each interacts with the others to help readers come to their own conclusions.
No remarriage after divorce / Gordon J. Wenham -- Remarriage for adultery or desertion / William A. Heth -- Remarriage for circumstances beyond adultery or desertion / Craig S. Keener.
Includes bibliographical references (p. 143-144) and indexes.
Keywords: Remarriage -- Religious aspects -- Christianity